Algebraische Zahlentheorie: 27.7. bis 2.8.1969 - Roquette, Peter (Tagungsbericht, 1969)
C. Arf, Ankara; I. V. Armitage, London; K. Barner, Stuttgart; H. Behr, Göttingen; H. Benz, Hamburg; H. Brückner, Hamburg; F. Chatelet, Besancon; B. Divis, Heidelberg; P. K. J. Draxl, Göttingen; A. Fröhlich, London; W.-D. Geyer, Heidelberg; F. Halter-Koch, Geyen; G. Harder, Bonn; M. Hazewinkel, Amsterdam; M. Ikeda, Ankara; K. Kiyek, Saarbrücken; K. Lakkis, Thessaloniki; A. Leutbecher, Münster; E. Lutz, Grenoble; J. Martinet, Bordeaux; H. Mathieu, Saarbrücken; E. Maus, Göttingen; H.-J. Nastold, Münster; J. Neukirch, Bonn; M. Peters, Hamburg; H. Popp, Heidelberg; P. Roquette, Heidelberg; K.-O. Stöhr, Bonn; G. Tamme, Bovenden; R. W. van der Waall, Nijmegen; H. J. Zassenhaus, Heidelberg